Development of Working Memory Maintenance - Geier, Charles F; Garver, Krista; Terwilliger, Robert; Luna, Beatriz (Journal of neurophysiology, 2009)
Laboratory of Neurocognitive Development, Department of Psychiatry and Psychology, Center for the Neural Basis of Cognition, University of Pittsburgh, Pittsburgh, Pennsylvania Submitted 15 June 2008; accepted in final form 20 October 2008 The neural circuitry supporting mature visual spatial working memory (VSWM) has been well delineated in nonhuman primates and in human adults. However, we still have limited understanding about developmental change through adolescence in this network. We present results from a fast event-related functional MRI (fMRI) study aimed at characterizing developmental changes in brain mechanisms supporting VSWM across different delay periods. Forty-three healthy subjects (17 adults, 18–30 yr; 13 adolescents, 13–17 yr; 13 children, 8–12 yr) were scanned as they performed an oculomotor delayed response (ODR) task with short (2.5 s) and long (10 s) delay period trials. Results showed that all age groups recruited a common network of regions to support both delay trials, including frontal, parietal, and temporal regions, indicative of a core circuitry needed to perform the task. Several age-related differences were found in the recruitment of regions, supporting short delay trials, including fronto-caudal areas, which could contribute to known differences in initial memory-guided saccade precision. To support extended delay trials, adults primarily recruited additional posterior parietal cortex (PPC), whereas children and adolescents recruited a considerably more extensive distributed circuitry. Our findings indicate that brain processes supporting basic aspects of working memory across cortex are established by childhood. We also find evidence for continued immaturities in systems supporting working memory precision, reflected by differences in the circuitry recruited by children and by continued refinement of fronto-insular-temporal regions recruited by adolescents. Taken together, these results suggest distinct developmental changes in the circuitry supporting visual spatial working memory. Address for reprint requests and other correspondence: C. Geier, Univ. of Pittsburgh, 121 Meyran Ave., Loeffler Bldg., Rm. 113, Pittsburgh, PA 15213 (E-mail: geiercfatupmc.edu )